PETG material for optical mirror surface material and preparation method of PETG material

A PETG material with enhanced optical properties and impact resistance is achieved through a specific composition and preparation process, addressing issues of refractive index instability and adhesion in existing PETG materials for optical mirrors.

CN119241999AActive Publication Date: 2025-01-03DONG GUAN WANSUCHENG PLASTIC CO LTD

Patent Information

Application Number
CN202411383613.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing PETG materials for optical mirrors suffer from uneven refractive index, instability, low hardness, susceptibility to scratches and wear, and poor adhesion, affecting optical performance and reliability.

Method used

A PETG material composed of specific raw materials including transparent polyester resin, antioxidant, lubricant, anti-yellowing agent, plastic brightener, polymer resin, nucleating agent, and modified glass fiber, with a controlled preparation process, enhances optical properties, toughness, and impact resistance.

Benefits of technology

The PETG material achieves high light transmittance of over 90%, excellent tensile strength, and good impact resistance, suitable for high-transparency applications with improved processability and durability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of PETG materials, in particular to a PETG material for an optical mirror surface material and a preparation method of the PETG material, and the PETG material comprises the following raw materials in parts by weight: 30-60 parts of transparent polyester resin, 1-3 parts of an antioxidant, 0.5-2.5 parts of a lubricant, 0.5-1.5 parts of an anti-yellowing agent, 1-3 parts of a plastic brightener, 5-10 parts of polymer resin, 1-3 parts of a nucleating agent and 5-10 parts of modified glass fiber. The PETG material disclosed by the invention has excellent optical performance, high-gloss surface and low turbidity, and the light transmittance of the PETG material can reach 90% or above; meanwhile, the material also has relatively good toughness, excellent tensile property and relatively good impact resistance; the prepared PETG material can be used for preparing a GAG three-layer co-solvent tablet, so that the GAG three-layer co-solvent tablet is good in transparency and texture, and is suitable for products requiring high transparency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PETG materials, and in particular to a PETG material for optical mirror material and a preparation method thereof. Background Art

[0002] Highly transparent polymer materials refer to polymer materials with a transmittance of more than 80% in daily light. Such materials are widely used in optical components, packaging, construction, medical supplies, optical fibers, and optical disc materials due to their unique optical properties. In recent years, the requirements for transparent polymer materials have become increasingly higher, and the demand has increased dramatically. Common transparent polymer materials are mainly transparent PP, PETG / PCTG, PC, PMMA, and polycycloolefins. Among them, PETG is a non-crystalline copolyester. The commonly used comonomer of PETG is 1,4-cyclohexanedimethanol (CHDM), the full name of which is polyethylene terephthalate-1,4-cyclohexanedimethanol. PETG has more 1,4-cyclohexanedimethanol comonomers than PET, and more ethylene glycol comonomers than PCT. Therefore, the performance of PETG is very different from that of PET and PCT. PETG sheet has outstanding toughness and high impact strength, which is 3 to 10 times that of modified polyacrylates. It has a wide processing range, high mechanical strength and excellent flexibility. Compared with PVC, it has high transparency, good gloss and is easy to print. It is a new generation of environmentally friendly plastics. As an important optical resin, PETG has gradually entered high-end fields such as packaging, medical, and optical lenses. However, the refractive index may be uneven or unstable during the synthesis process, resulting in irregular refraction of light when passing through the material, affecting the consistency of optical performance. The hardness of PETG material is relatively low, and it is easy to get scratches and wear during the synthesis and subsequent processing, reducing the service life and quality of the optical mirror. In addition, when bonding or coating with other materials, PETG material may have poor adhesion, affecting the overall performance and reliability of the optical mirror.

[0003] Therefore, the development of a new type of PETG material for optical mirror material is of great significance to the sustainable development of this field. Summary of the invention

[0004] In order to overcome the shortcomings and deficiencies in the prior art, the object of the present invention is to provide a PETG material for optical mirror material, the PETG material has excellent optical properties, high gloss surface and low turbidity, and its light transmittance can reach more than 90%; at the same time, it also has good toughness, excellent tensile resistance and good impact resistance.

[0005] The object of the present invention is to provide a method for preparing a PETG material for an optical mirror material. The method is simple and efficient, easy to operate and control, has high product quality, and is conducive to industrial production.

[0006] The purpose of the present invention is achieved through the following technical scheme: a PETG material for optical mirror material, comprising the following raw materials in parts by weight: 30-60 parts of transparent polyester resin, 1-3 parts of antioxidant, 0.5-2.5 parts of lubricant, 0.5-1.5 parts of anti-yellowing agent, 1-3 parts of plastic brightener, 5-10 parts of polymer resin, 1-3 parts of nucleating agent, and 5-10 parts of modified glass fiber.

[0007] The PETG material in the present invention has excellent optical properties, high gloss surface and low turbidity, and its light transmittance is close to 92%; it also has good toughness, excellent tensile strength and good impact resistance, and can be used to prepare a GAG three-layer co-agent sheet, so that the prepared GAG three-layer co-agent sheet has good transparency, the transparency can reach more than 90%, good texture, and is suitable for products requiring high transparency. It has excellent impact resistance and rigidity, and the material is hard and durable, suitable for uses with high impact resistance, and has excellent processability. It can be processed by sawing, die cutting, drilling and laser cutting, and can also be cold-bent and hot-bent, bonded, welded and polished, printed and coated, and cold bending does not self-degradate, and the appearance is bright. It has good thermoformability and can be formed without preheating. It has high precision, a shrinkage rate of about 0.5%, good deep formability, no cracking and uniform thickness. Among them, the transparent polyester resin used as the base material has excellent mechanical properties and high transparency; the addition of modified glass fiber effectively improves the strength of PP material. At the same time, due to the good compatibility between modified glass fiber and transparent polyester resin and polymer resin, the synergistic combination of modified glass fiber and nucleating agent can achieve the improvement of the tensile strength of PETG material. It also effectively improves the compatibility between various additives and transparent polyester resin, effectively avoids the problem of various additives reducing the surface flatness of PP material, and improves product quality; nucleating agent promotes the crystallization of PETG (decomposes in PETG melt to generate new substances, these substances as crystallization cores promote the crystallization of PETG), improves the crystallinity and heat resistance of the material, improves the optical properties of the material, reduces the haze of the material, and improves the transparency.

[0008] Preferably, the transparent polyester resin is one of PETGCR-5511 and PETG CR-5531 or a mixture of the two.

[0009] Preferably, the transparent polyester resin is a non-crystalline copolyester resin prepared by polymerization of ethylene glycol, terephthalic acid, 1,4-cyclohexanedimethanol and a catalyst.

[0010] Preferably, the catalyst is at least one of antimony oxide, antimony glycol, antimony acetate, stannous chloride, stannous octoate, germanium chloride and germanium oxide.

[0011] Preferably, the molar ratio of the ethylene glycol, terephthalic acid and 1,4-cyclohexanedimethanol is 1.0:1.0-4.0:0.3-0.7.

[0012] Preferably, the polymerization includes pre-polycondensation and polycondensation, the temperature during pre-polycondensation is 150-220° C., and the pre-polycondensation time is 30-120 min; the temperature during polycondensation is 200-260° C., and the polycondensation time is 1-4 h.

[0013] The transparent polyester resin in the present invention is prepared by the polycondensation reaction of ethylene glycol, terephthalic acid and 1,4-cyclohexanedimethanol. It is different from the previous structure in which a dibasic acid and a diol react to form an ester bond and a polycondensation reaction to form a polymer chain in that a part of the ethylene glycol in the present invention is replaced by cyclohexanedimethanol (CHDM). The role of adding CHDM is to prevent crystallization and improve processing performance, toughness, transparency and chemical resistance.

[0014] Preferably, the antioxidant is at least one of a phenolic antioxidant 1010 and a phosphite antioxidant 168 .

[0015] The antioxidant used in the present invention can prevent the PETG material from being oxidized during processing and use, extend the service life of the material, inhibit yellowing, degradation and the like caused by oxidation of the material, and maintain the optical and mechanical properties of the material.

[0016] Preferably, the lubricant is at least one of white mineral oil, silicone powder, stearic acid and its salts, paraffin, hydrocarbons, ethylene-vinyl acetate copolymer, and ethylene-acrylic acid copolymer.

[0017] The lubricant used in the present invention can improve the fluidity of the PETG material during processing, reduce the processing difficulty, reduce the friction between the PETG material and the processing equipment, and prevent the material from overheating, degradation and other problems due to friction during processing; adding a certain amount of lubricant as an auxiliary material is conducive to extrusion molding into coils or sheets.

[0018] Preferably, the polymer resin is composed of polyethylene naphthalate, epoxy resin and PET in a mass ratio of 0.8-1.2:0.4-0.8:0.3-0.7.

[0019] The polymer resin of the present invention adopts polyethylene naphthalate (PEN), which is similar to PET, but the benzene ring in PET is replaced by a naphthalene ring with greater rigidity in the molecular chain, which makes PEN have a higher glass transition temperature, better heat resistance and higher physical and mechanical properties. In the transparent PETG material, the addition of PEN can improve the overall heat resistance of the material, so that it can be used in a higher temperature environment, and expand the application range of the material; PEN has good optical properties, and the characteristics of its molecular structure make the material have a higher transmittance in the visible light range and can effectively block the transmission of ultraviolet rays. In the transparent PETG material, the addition of PEN can further improve the transparency and optical purity of the material, and at the same time enhance the anti-ultraviolet performance of the material and reduce ultraviolet rays. The influence of the line on the packaging contents; epoxy resin has a strong bonding ability and can be closely combined with PEN, PET and other additives to improve the integrity and stability of the material. In the synthesis process of transparent PETG material, epoxy resin can be used as a binder to enhance the interaction between the components and make the structure of the material denser, thereby improving the mechanical strength and chemical resistance of the material; finally, PET is a common thermoplastic polyester in transparent PETG material. PET, as one of the main ingredients, provides the material with basic physical properties and processing properties, so that the material can meet the requirements of various molding processes, such as injection molding, extrusion, blow molding, etc.; by adjusting the ratio of PET to PEN and epoxy resin, the performance balance of transparent PETG material can be adjusted.

[0020] Preferably, the nucleating agent is at least one of carboxylate nucleating agents, sorbitol nucleating agents, and polymer nucleating agents.

[0021] Preferably, the anti-yellowing agent is prepared by loading hindered amine light stabilizer (HALS) onto the surface of nano-silicon dioxide or nano-zinc oxide by physical adsorption.

[0022] After the anti-yellowing agent in the present invention is compounded with the PETG material, the nanoparticles can improve the dispersibility and stability of the anti-yellowing agent. At the same time, the nanoparticles themselves may also have certain anti-yellowing properties, thereby synergistically improving the anti-yellowing effect of the PETG material.

[0023] Preferably, the modified glass fiber is prepared by the following method: A1. Take glass fiber, wash the glass fiber with deionized water, and perform plasma etching on the washed glass fiber to obtain glass fiber after preliminary etching; wherein the plasma etching treatment conditions are: the plasma gas is one of nitrogen and argon, the power density is 200-300W, the pressure is 300-1000Pa, and the etching time is 15-30min. A2, acrylic acid is made into an acrylic acid solution with a mass concentration of 10-20%, and then the glass fiber after preliminary etching is immersed in it, the temperature is maintained at 70-120°C, vacuumed and pressurized to 800-1200Pa for reaction for 20-40min, and then cleaned with deionized water, dried, and a pre-treated product is obtained for standby use; A3. Take an appropriate amount of phosphoric acid solution and soak the pretreated material in it and stir for 10-20 minutes. Take out the pretreated material, wash and dry it, then add it to an ethanol solution of coupling agent KH550 with a concentration of 0.5g / ml, ultrasonically disperse it, and then put the dispersed mixture into a vacuum drying oven at 70-80°C to dry it to obtain modified glass fiber.

[0024] In the present invention, the glass fiber is first etched by plasma etching. The surface activity of the glass fiber can be enhanced by adding acrylic acid solution. Acrylic acid has active groups such as carboxyl groups. During the soaking process, it can chemically react or physically adsorb with substances on the surface of the glass fiber. This interaction can change the surface chemical properties of the glass fiber and increase its surface activity. Therefore, in the subsequent etching process, the etchant is more likely to contact and react with the surface of the glass fiber, thereby improving the efficiency and uniformity of etching. In addition, the acrylic acid solution can also improve the wettability of the glass fiber: the surface of the glass fiber usually has a certain hydrophobicity, which may cause etching. The spreading and penetration of the agent on its surface are limited. After adding acrylic acid for soaking, the wettability of the glass fiber can be improved, so that the etchant can spread and penetrate better on the surface of the glass fiber, ensuring that the etching reaction is carried out evenly on the entire glass fiber surface, avoiding the occurrence of local uneven etching; the coating or adsorption layer formed by acrylic acid on the surface of the glass fiber can play a protective role to a certain extent, reducing the direct erosion of the etchant on the glass fiber body, thereby maintaining the structural integrity and a certain mechanical strength of the glass fiber; acrylic acid may synergize with the etchant to promote the etching reaction, thereby accelerating the etching reaction rate and improving the etching effect. The role of the pretreatment of the etched glass fiber with phosphoric acid solution is mainly to clean and activate the surface of the glass fiber: some etching products and impurities may remain on the surface of the etched glass fiber. When it is soaked in phosphoric acid solution, phosphoric acid can react chemically with these residual substances and dissolve and remove them, thereby playing a role in cleaning the surface of the glass fiber. At the same time, the treatment with phosphoric acid can also break some chemical bonds on the surface of the glass fiber, generate new active sites, such as hydroxyl groups, etc., improve the activity of the surface of the glass fiber, and prepare for the subsequent grafting reaction of the silane coupling agent. In addition, the glass fiber itself has a certain degree of hydrophobicity, which will affect its bonding effect with the subsequent treatment agent. Phosphoric acid solution can improve the wettability of glass fiber, making the surface of glass fiber easier to be infiltrated by the subsequent silane coupling agent solution, ensuring that the silane coupling agent can be evenly distributed on the surface of glass fiber. When the silane coupling agent is added to the glass fiber after being treated with phosphoric acid solution, its hydrolyzable group will undergo hydrolysis reaction under certain conditions (such as the presence of water) to generate silanol (Si(OH)n). These silanols can undergo condensation reaction with active groups such as hydroxyl groups generated on the surface of glass fiber due to phosphoric acid treatment, thereby forming a chemical bond connection on the surface of glass fiber to form a "molecular bridge". One end of the silane coupling agent is firmly bonded to the surface of glass fiber, and the organic functional group at the other end extends outward. When it is subsequently compounded with polyester resin and polymer resin, these organic functional groups can react chemically or physically with the resin molecules, just like building a "molecular bridge" between inorganic glass fiber and organic resin, thereby greatly improving the interfacial bonding between glass fiber and resin and improving the performance of composite materials.

[0025] In summary, the above-mentioned modification method can effectively modify the glass fiber, improve its compatibility and interface bonding force with organic materials, so that the final composite material has better performance.

[0026] The present invention also provides a method for preparing a PETG material for an optical mirror material, comprising the following steps: S1. Place the transparent polyester resin in a drying machine at 65-70°C, dry for 3-6 hours, control the moisture content to be less than 0.1%, and set aside; S2, take the dried transparent polyester resin, add the transparent polyester resin, antioxidant, lubricant, and nucleating agent into a mixer according to weight and mix for 10-20 minutes, then add the anti-yellowing agent, plastic brightener, and polymer resin and continue mixing and stirring for 20-40 minutes for standby use; S3, the mixed material is fed through a twin-screw extruder as the main feed, and the modified glass fiber is fed through the side feed, and the blending and granulation are performed; wherein the temperature of the twin-screw extruder is set as follows: zone 1: 190±5°C; zone 2: 200±10°C; zone 3: 220±10°C; zone 4: 220±10°C; die head temperature: 220±10°C; screw speed is 300-380r / min; PETG material is obtained by extrusion and granulation.

[0027] The beneficial effects of the present invention are as follows: the PETG material of the present invention has excellent optical properties, a high gloss surface and low turbidity, and its light transmittance can reach more than 90%; at the same time, it also has good toughness, excellent tensile resistance and good impact resistance.

[0028] The preparation method of the PETG material for optical mirror material of the present invention is simple and efficient, and the operation and control are convenient, the produced product is high in quality, and it is conducive to industrial production. DETAILED DESCRIPTION

[0029] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0030] A PETG material for optical mirror material comprises the following raw materials in parts by weight: 30 parts of transparent polyester resin, 1 part of antioxidant, 0.5 part of lubricant, 0.5 part of anti-yellowing agent, 1 part of plastic brightener, 5 parts of polymer resin, 1 part of nucleating agent and 5 parts of modified glass fiber.

[0031] The transparent polyester resin is PETGCR-5511.

[0032] The antioxidant is phenolic antioxidant 1010.

[0033] The lubricant is white mineral oil.

[0034] The polymer resin is composed of polyethylene naphthalate, epoxy resin and PET in a mass ratio of 0.8:0.4:0.3.

[0035] The nucleating agent is a carboxylate salt, and the carboxylate salt is preferably a 101 sodium carboxylate nucleating agent provided by Dongguan Baolimei Plastic Co., Ltd.

[0036] The anti-yellowing agent is prepared by loading a hindered amine light stabilizer (HALS) onto the surface of nano-silicon dioxide or nano-zinc oxide by physical adsorption. The modified glass fiber is prepared by the following method: A1. Take glass fiber, wash the glass fiber with deionized water, and perform plasma etching on the washed glass fiber to obtain glass fiber after preliminary etching; wherein the plasma etching treatment conditions are: plasma gas is nitrogen, power density is 200-300W, pressure is 300Pa, etching time is 15min, A2. Prepare acrylic acid into an acrylic acid solution with a mass concentration of 10%, and then immerse the glass fiber after preliminary etching in the acrylic acid solution, maintain the temperature at 70°C, evacuate and pressurize to 800Pa for 20 minutes, then wash with deionized water, dry and obtain a pre-treated product for standby use; A3. Take an appropriate amount of phosphoric acid solution to soak the pretreated material in it and stir for 10 minutes. Take out the pretreated material, wash and dry it, then add it to an ethanol solution of coupling agent KH550 with a concentration of 0.5 g / ml, ultrasonically disperse it, and then put the dispersed mixture into a vacuum drying oven at 70°C to dry it to obtain modified glass fiber.

[0037] A method for preparing PETG material for optical mirror material comprises the following steps: S1. Place the transparent polyester resin in a drying machine at 65°C and dry for 3 hours, controlling the moisture content to be less than 0.1% for later use; S2, take the dried transparent polyester resin, add the transparent polyester resin, antioxidant, lubricant, and nucleating agent into a mixer according to weight and mix for 10 minutes, then add the anti-yellowing agent, plastic brightener, and polymer resin and continue mixing and stirring for 20 minutes for standby use; S3, the mixed material is fed through a twin-screw extruder as the main feed, and the modified glass fiber is fed through the side feed, and the blending and granulation are performed; wherein the temperature of the twin-screw extruder is set as follows: zone 1: 190±5°C; zone 2: 200±10°C; zone 3: 220±10°C; zone 4: 220±10°C; die head temperature: 220±10°C; screw speed is 300-380r / min; PETG material is obtained by extrusion and granulation.

[0038] A PETG material for optical mirror material comprises the following raw materials in parts by weight: 45 parts of transparent polyester resin, 2 parts of antioxidant, 2.0 parts of lubricant, 1.0 parts of anti-yellowing agent, 2 parts of plastic brightener, 8 parts of polymer resin, 2 parts of nucleating agent and 8 parts of modified glass fiber.

[0039] The transparent polyester resin is a non-crystalline copolyester resin prepared by polymerization of ethylene glycol, terephthalic acid, 1,4-cyclohexanedimethanol and a catalyst.

[0040] The catalyst is antimony glycol.

[0041] The molar ratio of the ethylene glycol, terephthalic acid and 1,4-cyclohexanedimethanol is 1.0:2.0:0.5.

[0042] The polymerization includes pre-condensation and polycondensation. The temperature of the pre-condensation is 200° C. and the pre-condensation time is 60 minutes. The temperature of the polycondensation is 240° C. and the polycondensation time is 2 hours.

[0043] The antioxidant is phenolic antioxidant 1010.

[0044] The lubricant is composed of paraffin, ethylene-vinyl acetate copolymer and ethylene-acrylic acid copolymer in a mass ratio of 0.5:0.7:0.3.

[0045] The polymer resin is composed of polyethylene naphthalate, epoxy resin and PET in a mass ratio of 1.0:0.6:0.5.

[0046] The nucleating agent is sorbitol, and the sorbitol is preferably a WBQ-88 sorbitol pp transparent nucleating agent provided by Guangdong Weilinna New Materials Technology Co., Ltd.

[0047] The anti-yellowing agent is prepared by loading a hindered amine light stabilizer (HALS) onto the surface of nano-silicon dioxide or nano-zinc oxide by physical adsorption. The modified glass fiber is prepared by the following method: A1. Take a glass fiber, wash the glass fiber with deionized water, and perform plasma etching on the washed glass fiber to obtain a glass fiber after preliminary etching; wherein the plasma etching treatment conditions are: the plasma gas is nitrogen, the power density is 250W, the pressure is 600Pa, and the etching time is 25min. A2, acrylic acid is made into an acrylic acid solution with a mass concentration of 15%, and then the glass fiber after preliminary etching is immersed in it, the temperature is maintained at 100°C, and the vacuum pressure is increased to 1000Pa to react for 30 minutes, and then it is cleaned with deionized water and dried to obtain a pre-treated product for standby use; A3. Take an appropriate amount of phosphoric acid solution to soak the pretreated material in it and stir for 15 minutes. Take out the pretreated material, wash and dry it, then add it to an ethanol solution of coupling agent KH550 with a concentration of 0.5 g / ml, ultrasonically disperse it, and then put the dispersed mixture into a vacuum drying oven at 75°C to dry it to obtain modified glass fiber.

[0048] A method for preparing PETG material for optical mirror material comprises the following steps: S1. Place the transparent polyester resin in a drying machine at 68°C and dry for 5 hours, controlling the moisture content to be less than 0.1% for later use; S2, take the dried transparent polyester resin, add the transparent polyester resin, antioxidant, lubricant, and nucleating agent into a mixer according to weight and mix for 15 minutes, then add the anti-yellowing agent, plastic brightener, and polymer resin and continue mixing and stirring for 30 minutes for standby use; S3, the mixed material is fed through a twin-screw extruder as the main feed, and the modified glass fiber is fed through the side feed, and the blending and granulation are performed; wherein the temperature of the twin-screw extruder is set as follows: zone 1: 190±5°C; zone 2: 200±10°C; zone 3: 220±10°C; zone 4: 220±10°C; die head temperature: 220±10°C; screw speed is 300-380r / min; PETG material is obtained by extrusion and granulation.

[0049] A PETG material for optical mirror material comprises the following raw materials in parts by weight: 60 parts of transparent polyester resin, 3 parts of antioxidant, 2.5 parts of lubricant, 1.5 parts of anti-yellowing agent, 3 parts of plastic brightener, 10 parts of polymer resin, 3 parts of nucleating agent and 10 parts of modified glass fiber.

[0050] The transparent polyester resin is a non-crystalline copolyester resin prepared by polymerization of ethylene glycol, terephthalic acid, 1,4-cyclohexanedimethanol and a catalyst.

[0051] The catalyst is stannous octoate.

[0052] The molar ratio of the ethylene glycol, terephthalic acid and 1,4-cyclohexanedimethanol is 1.0:4.0:0.7.

[0053] The polymerization includes pre-condensation and polycondensation. The temperature during pre-condensation is 220° C. and the pre-condensation time is 30 minutes. The temperature during polycondensation is 260° C. and the polycondensation time is 4 hours.

[0054] The antioxidant is phenolic antioxidant 1010.

[0055] The lubricant is silicone powder.

[0056] The polymer resin is composed of polyethylene naphthalate, epoxy resin and PET in a mass ratio of 1.2:0.8:0.7.

[0057] The nucleating agent is a carboxylate salt, and the carboxylate salt is preferably a 101 sodium carboxylate nucleating agent provided by Dongguan Baolimei Plastic Co., Ltd.

[0058] The anti-yellowing agent is prepared by loading a hindered amine light stabilizer (HALS) onto the surface of nano-silicon dioxide or nano-zinc oxide by physical adsorption. The modified glass fiber is prepared by the following method: A1. Take a glass fiber, wash the glass fiber with deionized water, and perform plasma etching on the washed glass fiber to obtain a glass fiber after preliminary etching; wherein the plasma etching treatment conditions are: the plasma gas is one of nitrogen and argon, the power density is 300W, the pressure is 1000Pa, and the etching time is 30min. A2. Prepare acrylic acid into an acrylic acid solution with a mass concentration of 20%, and then immerse the glass fiber after preliminary etching in the acrylic acid solution, maintain the temperature at 120°C, evacuate and pressurize to 1200Pa, react for 40 minutes, then wash with deionized water, dry, and obtain a pre-treated product for standby use; A3. Take an appropriate amount of phosphoric acid solution to soak the pretreated material in it and stir it for 20 minutes. Take out the pretreated material, wash and dry it, then add it to an ethanol solution of coupling agent KH550 with a concentration of 0.5g / ml, ultrasonically disperse it, and then put the dispersed mixture into a vacuum drying oven at 80°C to dry it to obtain modified glass fiber.

[0059] A method for preparing PETG material for optical mirror material comprises the following steps: S1. Place the transparent polyester resin in a drying machine at 70° C. and dry for 6 hours, controlling the moisture content to be less than 0.1% for later use; S2, take the dried transparent polyester resin, add the transparent polyester resin, antioxidant, lubricant, and nucleating agent into a mixer according to weight and mix for 20 minutes, then add the anti-yellowing agent, plastic brightener, and polymer resin and continue mixing and stirring for 40 minutes for standby use; S3, the mixed material is fed through a twin-screw extruder as the main feed, and the modified glass fiber is fed through the side feed, and the blending and granulation are performed; wherein the temperature of the twin-screw extruder is set as follows: zone 1: 190±5°C; zone 2: 200±10°C; zone 3: 220±10°C; zone 4: 220±10°C; die head temperature: 220±10°C; screw speed is 300-380r / min; PETG material is obtained by extrusion and granulation.

[0060] Battery separators.

[0061] Comparative Example 1 The difference between this comparative example and the above-mentioned Example 2 is that the raw material of the PETG material in this comparative example uses conventional commercially available PN300 PETG instead of transparent polyester resin. The rest of the contents of this comparative example are the same as those in Example 2 and will not be repeated here.

[0062] Comparative Example 2 The difference between this comparative example and the above-mentioned embodiment 2 is that no polymer resin is added to the raw material of the PETG material of this comparative example. The rest of the contents of this comparative example are the same as those of embodiment 2 and will not be repeated here.

[0063] Comparative Example 3 The difference between this comparative example and the above-mentioned Example 2 is that conventional glass fiber is used instead of modified glass fiber in the raw material of the PETG material of this comparative example, and the remaining raw materials are mixed according to the proportions of Example 2. The rest of the contents of this comparative example are the same as those of Example 2 and will not be repeated here.

[0064] The PETG materials obtained in Example 2 and Comparative Example 1 were placed in a mold, hot pressed, cooled, and demolded to obtain samples for performance testing. The results are shown in Table 1 below: Fluidity: Refer to GB / T 3682 2000 "Determination of mass flow rate and volume flow rate of thermoplastic melts"; Bending strength: tested in accordance with GB9341 test standard, the test condition is 2mm / min; Mechanical properties: tensile strength and tensile elongation at break are tested in accordance with GB / T1040.3.

[0065] The light transmittance was measured according to GB / T2410 2008, and the sample size was 100×100×2mm.

[0066] Table 1 project Fluidity MFR[g·(10min-1)] Bending strength MPa Tensile strength MPa Tensile elongation at break / % Transmittance% Example 2 15.36 175 63.8 63 91 Comparative Example 1 14.28 153 58.4 47 78 The PETG materials obtained in Example 2 and Comparative Example 1 were placed in a mold, hot pressed, cooled, and demolded to obtain samples for performance testing. The results are shown in Table 2 below: Mechanical properties: tensile strength and tensile elongation at break are tested in accordance with GB / T1040.3; The light transmittance was measured according to GB / T2410 2008, and the sample size was 100×100×2mm.

[0067] Table 2 project Tensile strength MPA Tensile elongation at break % Transmittance% Example 2 63.8 63 91 Comparative Example 2 55.7 45 90 The PETG materials obtained in Example 2 and Comparative Example 1 were placed in a mold, hot pressed, cooled, and demolded to obtain samples for performance testing. The results are shown in Table 3 below: Mechanical properties: tensile strength and tensile elongation at break are tested in accordance with GB / T1040.3; Surface gloss: Tested in accordance with GB 8807 standard, the test condition is 60°.

[0068] Table 3 project Surface gloss GU Tensile strength MPa Tensile elongation at break % Transmittance% Example 2 86 63.8 63 91 Comparative Example 3 72 53.4 53 78 It can be seen from the data in Tables 1-3 that the PETG material prepared in Example 2 of the present invention has excellent light transmittance, which can reach more than 90%, and also has good toughness, excellent tensile strength, good toughness and impact resistance. By adding special transparent polyester resin, polymer resin and modified glass fiber to the raw materials for preparing the PETG material, the problems existing in the current PETG material are fundamentally solved.

[0069] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A PETG material for optical mirror material, characterized in that: The invention comprises the following raw materials in parts by weight: 30-60 parts of transparent polyester resin, 1-3 parts of antioxidant, 0.5-2.5 parts of lubricant, 0.5-1.5 parts of anti-yellowing agent, 1-3 parts of plastic brightener, 5-10 parts of polymer resin, 1-3 parts of nucleating agent and 5-10 parts of modified glass fiber.

2. The PETG material for optical mirror material according to claim 1, characterized in that: The transparent polyester resin is one of PETGCR-5511 and PETG CR-5531 or a mixture of the two.

3. The PETG material for optical mirror material according to claim 1, characterized in that: The transparent polyester resin is a non-crystalline copolyester resin prepared by polymerization of ethylene glycol, terephthalic acid, 1,4-cyclohexanedimethanol and a catalyst.

4. The PETG material for optical mirror material according to claim 3, characterized in that: The catalyst is at least one of antimony oxide, antimony glycol, antimony acetate, stannous chloride, stannous octoate, germanium chloride and germanium oxide.

5. The PETG material for optical mirror material according to claim 3, characterized in that: The molar ratio of the ethylene glycol, terephthalic acid and 1,4-cyclohexanedimethanol is 1.0:1.0-4.0:0.3-0.7; the polymerization includes pre-condensation and polycondensation, the temperature during the pre-condensation is 150-220°C, and the pre-condensation time is 30-120min; the temperature during the polycondensation is 200-260°C, and the polycondensation time is 1-4h.

6. The PETG material for optical mirror material according to claim 1, characterized in that: The antioxidant is at least one of phenolic antioxidants 1010 and phosphite antioxidants 168; the nucleating agent is at least one of carboxylate nucleating agents, sorbitol nucleating agents, and polymer nucleating agents.

7. The PETG material for optical mirror material according to claim 1, characterized in that: The lubricant is at least one of white mineral oil, silicone powder, stearic acid and its salts, paraffin, hydrocarbons, ethylene-vinyl acetate copolymer, and ethylene-acrylic acid copolymer.

8. The PETG material for optical mirror material according to claim 1, characterized in that: The polymer resin is composed of polyethylene naphthalate, epoxy resin and PET in a mass ratio of 0.8-1.2:0.4-0.8:0.3-0.

7.

9. The PETG material for optical mirror material according to claim 1, characterized in that: The modified glass fiber is prepared by the following method: A1. Take glass fiber, wash the glass fiber with deionized water, and perform plasma etching on the washed glass fiber to obtain glass fiber after preliminary etching; wherein the plasma etching treatment conditions are: the plasma gas is one of nitrogen and argon, the power density is 200-300W, the pressure is 300-1000Pa, and the etching time is 15-30min. A2, acrylic acid is made into an acrylic acid solution with a mass concentration of 10-20%, and then the glass fiber after preliminary etching is immersed in it, the temperature is maintained at 70-120°C, vacuumed and pressurized to 800-1200Pa for reaction for 20-40min, and then cleaned with deionized water, dried, and a pre-treated product is obtained for standby use; A3. Take an appropriate amount of phosphoric acid solution and soak the pretreated material in it and stir for 10-20 minutes. Take out the pretreated material, wash and dry it, then add it to an ethanol solution of coupling agent KH550 with a concentration of 0.5g / ml, ultrasonically disperse it, and then put the dispersed mixture into a vacuum drying oven at 70-80°C to dry it to obtain modified glass fiber.

10. A method for preparing the PETG material for optical mirror material according to any one of claims 1 to 9, characterized in that: The steps include: S1. Place the transparent polyester resin in a drying machine at 65-70°C, dry for 3-6 hours, control the moisture content to be less than 0.1%, and set aside; S2, take the dried transparent polyester resin, add the transparent polyester resin, antioxidant, lubricant, and nucleating agent into a mixer according to weight and mix for 10-20 minutes, then add the anti-yellowing agent, plastic brightener, and polymer resin and continue mixing and stirring for 20-40 minutes for standby use; S3, the mixed material is fed through a twin-screw extruder as the main feed, and the modified glass fiber is fed through the side feed, and the blending and granulation are performed; wherein the temperature of the twin-screw extruder is set as follows: zone 1: 190±5°C; zone 2: 200±10°C; zone 3: 220±10°C; zone 4: 220±10°C; die head temperature: 220±10°C; screw speed is 300-380r / min; PETG material is obtained by extrusion and granulation.

Citation Information

Patent Citations

  • PETG-PC alloy with high light transmittance and high toughness as well as preparation method and application of PETG-PC alloy

    CN114539740A

  • Interfacial reinforced continuous glass fiber reinforced PETG (polyethylene terephthalate glycol) resin unidirectional prepreg tape and preparation method thereof

    CN117186591A

  • Polyester resin composition, and molded artice manufactured therefrom

    KR1020110108979A

  • Polyester resin composition having good yellowing resistance and impact resistance

    WO2013100578A1

Cited By

  • Impact-resistant modified PETG polyester material and preparation method thereof

    CN119662001A